Odour-based discrimination of similarity at the major histocompatibility complex in birds. Issue 1846 (11th January 2017) - Leclaire, Sarah; Strandh, Maria; Mardon, Jérôme; Westerdahl, Helena; Bonadonna, Francesco
Abstract : Many animals are known to preferentially mate with partners that are dissimilar at the major histocompatibility complex (MHC) in order to maximize the antigen binding repertoire (or disease resistance) in their offspring. Although several mammals, fish or lizards use odour cues to assess MHC similarity with potential partners, the ability of birds to assess MHC similarity using olfactory cues has not yet been explored. Here we used a behavioural binary choice test and high-throughput-sequencing of MHC class IIB to determine whether blue petrels can discriminate MHC similarity based on odour cues alone. Blue petrels are seabirds with particularly good sense of smell, they have a reciprocal mate choice and are known to preferentially mate with MHC-dissimilar partners. Incubating males preferentially approached the odour of the more MHC-dissimilar female, whereas incubating females showed opposite preferences. Given their mating pattern, females were, however, expected to show preference for the odour of the more MHC-dissimilar male. Further studies are needed to determine whether, as in women and female mice, the preference varies with the reproductive cycle in blue petrel females. Our results provide the first evidence that birds can use odour cues only to assess MHC dissimilarity.